CONSERVATION AND MAINTENANCE CONCEPTS OF SOONG CHING LING’S DOLOMITE MARBLE STATUE IN SHANGHAI AND SUPPORTING SURVEY METHODS - T. Qin; Y. Wang; J. Li; Z. Tang; Z. Tang; S. Dai; S. Dai (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2021)
The dolomite marble statue of Madam Soong Ching Ling, Honorary Chairlady of the People’s Republic of China, is situated in the memorial square of Soong Ching Ling’s Mausoleum in Shanghai, China. The statue is composed of 4 pieces of white marble (Hanbaiyu) from Fangshan, Beijing. The statue, along with the mausoleum, has been listed as a national monument since 1982, yet severe deterioration occurred in recent years. In May 2018, a diagnostic investigation of the statue was carried out. Aided by advanced photogrammetry methods such as 3D modelling, macro photography and infrared thermography, all micro cracks were identified and labelled. Other advanced in-situ and laboratory surveys such as in-situ microscope, ultrasonic CT inspection, chalking evaluation test and mineralogical investigation were applied to further evaluate the condition. Based on analysis of all test results, conservation and maintenance concepts including a monitoring program specifically to control cracking has been developed. This concept was approved by the authorities and implemented in May 2019. After two years’ exposure, an evaluation of previous conservation and a new maintenance work were recently completed in April 2021. A long-term monitoring strategy as well as maintenance methods will be worked out based on the evaluation of all implemented efforts and climatic data.